Impact of State Children's Health Insurance Program on Fertility of Immigrant Women - Kabir Dasgupta; Keshar Ghimire; Alexander Plum (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2020)
Between 1997 and 2000, all states in the United States (US) enacted the State Children's Health Insurance Program (SCHIP) to provide publicly funded health insurance coverage for children in low income families. However, only 15 states including the District of Columbia chose to provide coverage for children of newly arrived immigrants in their SCHIP. We exploite the resulting state and time variation in the implementation of the program in a difference-in-differences framework to estimate the effect of a publicly funded children's health insurance benefit on immigrant women's fertility. While estimates from full samples show that the net effect of the program was indistinguishable from zero, we find a significant positive effect on the fertility of unmarried immigrant women, both at extensive and at intensive margin. Our findings have important policy implications for societies experiencing a persistent decline in fertility.
Keywords: I13; J13; 330; State Children's Health Insurance Program; Immigrant Fertility; Birth rate; Quantity-quality tradeoff